Ecopedagogia: implicações de uma escola sustentável na educação dos anos iniciais do ensino fundamental - Goin, Nadriéle (2020)
This article deals with the theme of Ecopedagogy, whose general objective is to identify the ways of implementing it in the early years of elementary school. The methodology used in this study has a qualitative approach and a method of producing data for bibliographic research. Today, children are increasingly connected to screens and disconnected with the nature that surrounds them. For this reason, Ecopedagogy is a tendency to make the traditional school more ecological, but it is not a simplistic task. Thus, understanding how Ecopedagogy can contribute to the implantation of a sustainable school is essential. From the readings carried out, we can conclude that it does not take much to make the school sustainable, this being a viable possibility for everyone. Ecopedagogy and the Earth Charter principles should be the guiding principles for school practices that aim to form planetary citizens, that is, that are able to see beauties beyond profit and that are concerned with the survival of humanity's great home.